2014
DOI: 10.7763/ijcea.2014.v5.342
|View full text |Cite
|
Sign up to set email alerts
|

Effects of RF Power and Treatment Time on Wettability of Oxygen Plasma-Treated Diamond-like Carbon Thin Films

Abstract: Abstract-Diamond-like carbon (DLC) thin films can be used in numerous industrial applications, including biomedical modified-surfaces with biocompatible and wetting properties. It is important to understand the surface properties of DLC thin films for these applications. In this study, oxygen (O 2 ) plasma treatment on DLC film surfaces is studied, taking into account the effects of radio frequency (RF) power and treatment time on wetting property. All the films were prepared on Si (100) wafers using a plasma-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…A similar study about the effect of plasma sputtering RF power on diamond-like carbon thin films was previously had been carried out by Jongwannasiri et al Based on the results of the study showed plasma treatment on DLC films surface influenced to thickness change, but not affect to structure of the films with various RF powers [24]. However, the limitation of this result didn't discuss about the effect of various plasma power on hardness of DLC films and only discuss the thickness of DLC films.…”
Section: Literature Review and Problem Statementmentioning
confidence: 58%
“…A similar study about the effect of plasma sputtering RF power on diamond-like carbon thin films was previously had been carried out by Jongwannasiri et al Based on the results of the study showed plasma treatment on DLC films surface influenced to thickness change, but not affect to structure of the films with various RF powers [24]. However, the limitation of this result didn't discuss about the effect of various plasma power on hardness of DLC films and only discuss the thickness of DLC films.…”
Section: Literature Review and Problem Statementmentioning
confidence: 58%
“…On the other hand, oxygen plasma treatment is an attractive and widely used technique on both the experimental and industrial scales to improve thin-film technology without introducing any complexity into the material stoichiometry [ 22 , 23 , 24 ]. Oxygen plasma treatment is a well-known method used to clean the substrates for the development of thin films, since the oxygen plasma treatment enhances the adhesion of thin films to the substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen plasma treatment is a well-known method used to clean the substrates for the development of thin films, since the oxygen plasma treatment enhances the adhesion of thin films to the substrates. The optimized oxygen plasma treatment process can enhance the thin film’s bonding strength (surface energy) and adequately modify the film surfaces for various microelectronics and optoelectronics devices without affecting the entire nanostructure of the devices [ 22 , 23 , 24 , 25 , 26 , 27 ]. J. W. Roh et al have reported that the oxygen plasma- assisted wafer bonding process is very effective and crucial for the fabrication of integrated optical waveguide isolators.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, oxygen plasma treatment is an attractive and widely used technique on both the experimental and industrial scales to improve thin-film technology without having any complexity into the material stoichiometry [19][20][21]. Oxygen plasma treatment is a well-known method used to clean the substrates for the development of thin films as the oxygen plasma treatment enhances the adhesion of the thin films to the substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen plasma treatment is a well-known method used to clean the substrates for the development of thin films as the oxygen plasma treatment enhances the adhesion of the thin films to the substrates. The optimized oxygen plasma treatment can enhance the thin film's bonding strength (surface energy) and adequately modify the film surfaces for various microelectronics and optoelectronics devices without affecting the entire nanostructures of the devices [19][20][21][22][23][24]. J. W. Roh et al have reported that the oxygen plasma assisted wafer bonding process is very effective and crucial for the fabrication of integrated optical waveguide isolators.…”
Section: Introductionmentioning
confidence: 99%